Exploring the students’ perception on the use of teaching factory method in English learning - Nodistya Septian Indrastana; Vigo Dewangga; Renata Kenanga Rinda (Journal of Applied Studies in Language, 2023)
The Economic development of a country is determined by the main factor, the human resources competitiveness. In preparing competent human resources, the strategic program to be undertaken by the government is to align competencies of  vocational higher education students with the needs of industrial competence. As a result, link and match between industry and higher-level vocational education could be achieved. The solution to prepare students to have competencies that are in accordance with industrial competence is by giving teaching factory (TEFA) method. It is a concept that aims to align manufacturing teaching to the needs of industrial practice. This study focuses on students’ perceptions on the use of teaching factory method in English learning, especially English for hotel and restaurant. This study adopts qualitative approach. Data were collected using questionnaires and interviews. The findings in this study reveal students' perceptions and responses on the use of teaching factory method. It shows that many of the students feel enthusiasm in attending English for hotel and restaurant using teaching factory method. It also shows that many of the students express that learning in English for hotel and restaurant encourage them to be actively participated in learning process. It can be concluded that most of the students have a positive impression about the use of teaching factory method in English learning, especially English for hotel and restaurant.